1991
DOI: 10.1164/ajrccm/143.6.1215
|View full text |Cite
|
Sign up to set email alerts
|

Spirometry in the Lung Health Study: 1. Methods and Quality Control

Abstract: The Lung Health Study is a randomized clinical trial designed to determine whether a smoking intervention program and prescription of an inhaled bronchodilator can reduce the annual rate of decline of FEV1 (FEV1 slope) in cigarette smokers with mild to moderate airflow limitation. During the recruitment period, spirometry measurements were obtained during three screening visits from 5,887 cigarette smokers 35 to 60 yr of age. To improve the statistical power of the study to detect significant differences in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
157
0
2

Year Published

1994
1994
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(161 citation statements)
references
References 12 publications
2
157
0
2
Order By: Relevance
“…A previous study in Latino Americans showed that asthma severity might be influenced by ancestry in Mexican Americans . Recognizing that there is no single measure that accurately captures all facets of asthma severity, pre-FEV 1 percent predicted has several advantages as a marker of asthma severity, including its objectivity and reproducibility (Enright et al 1991;Enright et al 1994;Kitch et al 2004). …”
Section: Discussionmentioning
confidence: 99%
“…A previous study in Latino Americans showed that asthma severity might be influenced by ancestry in Mexican Americans . Recognizing that there is no single measure that accurately captures all facets of asthma severity, pre-FEV 1 percent predicted has several advantages as a marker of asthma severity, including its objectivity and reproducibility (Enright et al 1991;Enright et al 1994;Kitch et al 2004). …”
Section: Discussionmentioning
confidence: 99%
“…Spirometry was performed with a rolling seal spirometer (Spirotech 500; Spirotech, Atlanta, GA, USA), with an intensive quality-control programme [14]. Measurements were made before and 10 min after two puffs of isoproterenol (200 mg total dose) from a metered dose inhaler.…”
Section: Methodsmentioning
confidence: 99%
“…In research settings where critical oversight is provided, test quality is maintained at a high level. It is common for ATS acceptability and reproducibility criteria to be met w90% of the time in both healthy individuals and those with respiratory diseases [7][8][9]. In settings without such training and oversight, however, such as primarycare offices, good test performance is less consistent.…”
Section: Methods Of Assessing Airflow Limitation: Current Recommendatmentioning
confidence: 99%
“…Good initial technician training and regular feedback to technicians are essential elements to maintaining good test quality in research settings and these practices should also work in clinical laboratories [8]. Software developed for research studies allows spirometry quality to be assessed rapidly and electronic feedback quickly returned to the technicians performing the tests [11].…”
Section: Methods Of Assessing Airflow Limitation: Current Recommendatmentioning
confidence: 99%